2010
DOI: 10.1089/ast.2009.0396
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Isolation of Extremotolerant Bacteria from the Clean Room Where Phoenix Spacecraft Components Were Assembled

Abstract: The microbial burden of the Phoenix spacecraft assembly environment was assessed in a systematic manner via several cultivation-based techniques and a suite of NASA-certified, cultivation-independent biomolecule-based detection assays. Extremotolerant bacteria that could potentially survive conditions experienced en route to Mars or on the planet's surface were isolated with a series of cultivation-based assays that promoted the growth of a variety of organisms, including spore formers, mesophilic heterotrophs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 31 publications
(35 reference statements)
3
63
0
Order By: Relevance
“…A key unanswered question for the robotic and human exploration of Mars is whether terrestrial microorganisms can adapt to and acquire the capability for active metabolism and replication at, the ϳ0.7-kPa atmospheric pressure at the martian surface. Diverse microbial communities including extremophiles and sporeformers have been recovered from spacecraft surfaces and processing facilities prior to launch of spacecraft to Mars (9,15,31), and the survival of some of these species during the Earth-to-Mars interplanetary transit phase is quite probable (23,24,26). However, upon landing on Mars, at least 13 separate biocidal factors in addition to low pressure are likely to be present on the martian surface (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…A key unanswered question for the robotic and human exploration of Mars is whether terrestrial microorganisms can adapt to and acquire the capability for active metabolism and replication at, the ϳ0.7-kPa atmospheric pressure at the martian surface. Diverse microbial communities including extremophiles and sporeformers have been recovered from spacecraft surfaces and processing facilities prior to launch of spacecraft to Mars (9,15,31), and the survival of some of these species during the Earth-to-Mars interplanetary transit phase is quite probable (23,24,26). However, upon landing on Mars, at least 13 separate biocidal factors in addition to low pressure are likely to be present on the martian surface (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies evaluating the effectiveness of sampling devices for the recovery of microorganisms from clean-room surfaces have used purified bacterial spores (8,9,11,12,29,32,34,39) or pure cultures of vegetative cells (7) as positive controls. However, such controls do not accurately represent the highly diverse microbial populations which can be expected in nearly all environments, including clean rooms (10,15,30,35). Additionally, whenever samples are collected for the purpose of molecular-analysis-based microbial monitoring, results will be affected not only by the presence of living cells but also by dead and decaying cells and spores, cellular debris, and indigenous biomolecules (e.g., nucleic acids, lipids, proteins, carbohydrates).…”
mentioning
confidence: 99%
“…Within category A, rRNA gene abundances remained at consistent levels (Յ10 5 16S rRNA gene copies/m 2 ), with the exception of two samples (GI-15 and GI-17; Table 1) which also gave the highest diversity. Previous studies have demonstrated that whenever spacecraft-associated surface samples yield fewer than ϳ1 ϫ 10 5 16S rRNA gene copies/m 2 , they can be expected to give rise to very few, if any, cultivable cells or spores (13,18). The results of this study support this observation.…”
Section: Resultsmentioning
confidence: 99%